Genetic Diversity, Habitat Relevance and Conservation Strategies of the Silver Carp in the Yangtze River by Simple Sequence Repeat - Luo, Yu-Ting; Fang, Di-An; Zhou, Yan-Feng; Xu, Dong-Po; Peng, Yun-Xin; Zhang, Min-Ying; Mao, Cheng-Cheng; Tang, Xue-Mei; Xu, Jun; You, Yang (Frontiers in Ecology and Evolution, 2022)
The spatial distribution of fish individuals is affected by habitat conditions and species ecological characteristics, and it also reflects the longtime adaptation to habitat at the phenotypic and genotypic level. As a typical river-lake migratory fish species, the silver carp habitat selection was determined by its migration preference and genetic features. In this study, 15 microsatellite fluorescent markers combined with capillary electrophoresis were used to analyze the genetic diversity, genetic differentiation, and structure of nature silver carp populations in the Sanzhou (SZ), Hukou (HK), Anqing (AQ), Zhenjiang (ZJ), and Rugao (RG) sections of the Yangtze River. The results showed that 15 microsatellite loci exhibited medium to high polymorphisms. The overall genetic diversity in the Yangtze River was high, with the average value of Shannon’s information index ranging from 1.559 to 1.668. The numbers of alleles (Ne) ranged from 1.630 to 10.100. The expected heterozygosity (He, 0.690–0.721) was higher than observed heterozygosity (Ho, 0.598–0.646), and the genetic variation mainly originated from within the population (94.69%). However, the entire population was in the state of heterozygous deletion, and HK, RG populations encountered the risk of inbreeding risk (F > 1). Interestingly, there was a distinct genetic structure for the population in the HK section, which indicated that local population has occurred to the silver carp in this river section, and they may also possess aggregation characteristics specific to the river-lake-connected (RLC) habitat. The results mostly support the conclusion that the RLC habitat is essential for geographic population formation. The potential impact of special habitats on natural populations should be considered, and continuous surveys on population dynamics should be performed.